2019
DOI: 10.21273/horttech04204-18
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Mechanical Pruning in Vineyards Maintains Fruit Composition while Reducing Labor Costs in ‘Merlot’ Grape Production

Abstract: A field study was conducted for three consecutive seasons in the hot climate of central California to assess the performance of ‘Merlot’ grapevine (Vitis vinifera) grafted onto ‘Freedom’ [Fresno 1613-59 × Dog Ridge 5 (27% V. vinifera hybrid)] during training system conversion to facilitate mechanization. The traditional head-trained and cane-pruned (CP) system was either retained or converted either to a bilateral cordon-trained, spur-pruned Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…Previous research suggested that to reach the maximum level of maturity, a leaf area to fruit ratio between 0.8 to 1.2 m 2 /kg was required for a single-canopy trellis system (Kliewer and Dokoozlian, 2005). In our study, there was no difference of leaf area to fruit ration between two water status zones and the first year had overall leaf to fruit ratio lower than 0.8 m 2 /kg consistent with previous findings that mechanically managed vineyards in warm regions may ripen fruit to technological maturity at lower values (Kurtural et al, 2019).…”
Section: Yield Componentssupporting
confidence: 92%
“…Previous research suggested that to reach the maximum level of maturity, a leaf area to fruit ratio between 0.8 to 1.2 m 2 /kg was required for a single-canopy trellis system (Kliewer and Dokoozlian, 2005). In our study, there was no difference of leaf area to fruit ration between two water status zones and the first year had overall leaf to fruit ratio lower than 0.8 m 2 /kg consistent with previous findings that mechanically managed vineyards in warm regions may ripen fruit to technological maturity at lower values (Kurtural et al, 2019).…”
Section: Yield Componentssupporting
confidence: 92%
“…Dormant pruning weight was collected during the dormant season (16 December); and crop load was calculated as the ratio between yield per vine (kg) and the pruning mass (kg) of each vine. Labor operations costs and gross income per hectare were calculated based on yield and net returns per hectare (California Department of Food and Agriculture, 2020; Kurtural et al, 2020) and methods presented elsewhere (Kurtural et al, 2019). Anthocyanin productivity (unit cost to produce anthocyanin) was calculated as reported by Cook et al (2015).…”
Section: Weather Conditionsmentioning
confidence: 99%
“…Dormant pruning is one of the most labor-intensive practices in vineyards 1,8 . It is estimated that about 80% of all labor operations costs in vineyards can be attributed to the combination of pruning and harvesting practices 27 .…”
Section: Winter Pruningmentioning
confidence: 99%
“…Research in interior and coastal California 1,8,27,[36][37][38] has shown that using one of the pruning management strategies described above would save between 60% to 80% of labor operation costs per acre compared to manual pruning alone 1,8,27,38 . In a study comparing traditional Guyot cane pruning, manual spur pruning and complete mechanization in Madera, CA researchers found that converting traditionally farmed systems will save 80% of labor operations cost without any differences in berry primary and secondary metabolites.…”
Section: Doi: 105344/catalyst202120011mentioning
confidence: 99%
See 1 more Smart Citation